Endodontic Management of a Maxillary Central Incisor with two Roots: A Case Report and Literature Review: maxillary central incisor with two roots - Namaei Ghasemi, Sajedeh; Forghani, Maryam; Karimpour, Sahar (Iranian Endodontic Journal, 2023)
Maxillary incisors are typically straightforward cases for root canal therapy. While it is commonly assumed that maxillary central incisors have a single root canal, they may occasionally exhibit variations in their root canal system anatomy. In this report, we present a case of a maxillary central incisor with multiple root canals and provide a review of relevant literature on this anatomical variation. A 13-year-old female with deep carious lesion in tooth 11 was admitted in Department of Endodontics. Following a precise clinical and radiographic examination, a maxillary central incisor with necrotic pulp and chronic apical periodontitis along with unusual root anatomy was found and considered for non-surgical root canal treatment. Successful treatment results depend on various factors and awareness of root canal system anatomy is one of them. Due to an increasing number of reported cases of maxillary central incisors with different anatomy, it is imperative to consider anatomical variations even in the most routine cases.